The cross-situational generalisation of learned helplessness : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Tuffin, Keith Francis (Massey University, 1982)
This study aimed to investigate the cross-situational generalisation of learned helplessness. The experiment was conducted in two distinct phases, with 90 first-year psychology students volunteering as subjects. In phase one, subjects were exposed to one of three pretreatment conditions; contingent reinforcement, noncontingent reinforcement and control. In the second phase the performance of these three groups was compared on a test task involving social interaction. Affective changes were noted (on the Multiple Affect Adjective Check List) following the first phase for helpless subjects. Helplessness failed to generalise across situations and no performance deficits were evident on the test task. The results did not support predictions of wide generality. The failure to demonstrate cross-situational generalisation was discussed in terms of the implications for learned helplessness theory.
Keywords: Helplessness (Psychology)